Psychological, social and lifestyle screening of people with low back pain treated by physiotherapists in a National Health Service musculoskeletal service: an audit. (2nd January 2023) - Singh, Gurpreet; McNamee, George; Sharpe, Laura; Lucas, Michael; Lewis, Paul; Newton, Christopher; O'Sullivan, Peter; Lin, Ivan; O'Sullivan, Kieran
Abstract: Purpose: Psychological, social and lifestyle (multidimensional) factors predict low back pain (LBP). The Short Form Örebro Musculoskeletal Questionnaire (SFÖQ) helps clinicians identify these factors in people with LBP and was mandated in a physiotherapy department at one NHS Hospital Trust in the UK. This study examined (i) use of the SFÖQ by physiotherapists with varying levels of clinical experience; (ii) whether psychological, social, and lifestyle factors were documented in patient records; and (iii) physiotherapists views on using the SFÖQ, and screening for these factors. Methods: A retrospective audit of the physiotherapy records of 100 people referred with LBP. Results: Eighty-one patient records were eligible for analysis. The SFÖQ was completed in 52 records. Fourteen of the completed SFÖQ's were used by physiotherapists. Screening for, and documentation of, multidimensional factors varied between factors ((i) psychological: cognitive (20%), emotional (26%); (ii) social (41%) and (iii) lifestyle (62%)). 67% of the most senior physiotherapists screened and documented emotional factors. Physiotherapists identified a lack of training, confidence and time as barriers to screening for multidimensional factors and using the SFÖQ. Conclusion: Physiotherapists rarely used the SFÖQ and did not consistently screen or document multidimensional factors. However, more senior physiotherapists more consistently screened and documented emotional factors.